2015
DOI: 10.1136/archdischild-2014-308080
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19 myocarditis in children: an observational study

Abstract: PVB19 can cause a devastating myocarditis in children. Children with fulminant myocarditis, ST segment changes or a short prodrome have the worst outcome. Transplantation may be considered, but is rarely required in the acute period if mechanical circulatory support is utilised. If the initial presentation is survived, recovery of the myocardium can occur even in those who had fulminant myocarditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 31 publications
2
11
0
1
Order By: Relevance
“…In accord with these results, viral presence had no influence on outcome in another study . In contrast, other studies have reported an association between B19V infection of the heart and high morbidity and mortality . The above results demonstrate that large gaps in knowledge still exist in cardiac B19V infection and children.…”
Section: Parvovirus B19‐related Heart Disease In Childrensupporting
confidence: 66%
See 1 more Smart Citation
“…In accord with these results, viral presence had no influence on outcome in another study . In contrast, other studies have reported an association between B19V infection of the heart and high morbidity and mortality . The above results demonstrate that large gaps in knowledge still exist in cardiac B19V infection and children.…”
Section: Parvovirus B19‐related Heart Disease In Childrensupporting
confidence: 66%
“…Clinical presentation of B19V‐related MC or heart failure in children is often more severe compared with adult presentation and outcome . However, EMB is performed infrequently in children with suspected MC . Therefore, data regarding B19V in EMB in children are scarce and are often incomplete.…”
Section: Parvovirus B19‐related Heart Disease In Childrenmentioning
confidence: 99%
“…B19V infection, detected most often by serological evidence of recent infection and sometimes by the detection of viral genomes in cardiac tissue, has been reported in myocarditis in the fetus (see the section on hydrops below), in infancy, during childhood, and among young adults (174,176,(832)(833)(834)(835)(836)(837)(838)(839)(840). In one center's series of 19 pediatric patients, the presenting symptoms were upper respiratory and gastrointestinal symptoms; all infected children had ventricular dysfunction, 2 died, and 3 required heart transplantation (176).…”
Section: Clinical Manifestations Diseases Caused By B19v Infectionmentioning
confidence: 99%
“…Interestingly, two peaks in occurrence were noted: in infants <1 year and in teenagers. Myocarditis in newborns is mainly caused by viral infection, such as enterovirus, parvovirus, or adenovirus (11).…”
Section: Indicationsmentioning
confidence: 99%